2009
DOI: 10.1002/bdrb.20197
|View full text |Cite
|
Sign up to set email alerts
|

Considerations in assessing the developmental and reproductive toxicity potential of biopharmaceuticals

Abstract: This report discusses the principles of developmental and reproductive toxicity (DART) testing for biopharmaceuticals. Biopharmaceuticals are large‐molecular‐weight proteins or peptides produced by modern biotechnology techniques incorporating genetic engineering and hybridoma technologies. The principles of DART testing for biopharmaceuticals are similar to those for small‐molecule pharmaceuticals and in general follow the regulatory guidance outlined in International Conference on Harmonisation of Technical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 76 publications
0
48
0
Order By: Relevance
“…In order to evaluate any potential effects of ustekinumab treatment during pregnancy, it was necessary to conduct developmental studies in cynomolgus macaques. The cynomolgus macaque is a species frequently used for the non-clinical safety evaluation of human therapeutic monoclonal antibodies (Chellman et al, 2009;Martin, 2008;Martin et al, 2007Martin et al, , 2009Wehner et al, 2009). The cynomolgus macaque is physiologically and endocrinologically similar to humans (Chellman et al, 2009;Weinbauer et al, 2008a,b).…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate any potential effects of ustekinumab treatment during pregnancy, it was necessary to conduct developmental studies in cynomolgus macaques. The cynomolgus macaque is a species frequently used for the non-clinical safety evaluation of human therapeutic monoclonal antibodies (Chellman et al, 2009;Martin, 2008;Martin et al, 2007Martin et al, , 2009Wehner et al, 2009). The cynomolgus macaque is physiologically and endocrinologically similar to humans (Chellman et al, 2009;Weinbauer et al, 2008a,b).…”
Section: Introductionmentioning
confidence: 99%
“…If reproductive toxicology studies are shown to be necessary and no potential alternative options to the NHP exist (e.g., rodent with the clinical or homologous protein 33 ) the approach proposed by Jarvis et al could be undertaken. 34,35 The paper describes an 'enhanced' PPND study design, which is conducted as a single study to replace the embryo fetal development (EFD) and the traditional PPND, which have historically function and cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal characteristics must be taken into account when selecting a species for toxicological studies in order to achieve the most similar toxic reactions to those of humans: should have a good reproductive capacity; number of animals required and associated costs; sexually mature, with the presence of semen checked prior to drug exposure; spermatogenesis of immature animals may be erroneously misinterpreted as impaired spermatogenesis; immature animals, rich in spermatogonia stem cells, could be excellent animal models for child medicines [52]; qualitative and quantitative measurements, such as hormonal levels [53], animal weight and overall health status, must be carefully examined; determine drug cell and tissue metabolism, and the pharmacological curve; define length of treatment and dose used; document late onset events such as chronic toxicity [54][55][56]. Despite the relevant importance for human diseases, experiments should also minimize animal suffering [57].…”
Section: Methodsmentioning
confidence: 99%